Speed, change of direction speed, and reactive agility of junior soccer players according to the level of competition - Andrasic, S.; Gusic, M.; Molnar, S. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: It is well documented that physical, technical and tactical skills successfully discriminate soccer players by competitive level. However, the majority of studies have focused on adolescent soccer players with biggest individual differences in growth and biological maturation. There is limited information for older adolescent players. Moreover, information regarding the potential level differences between elite and subelite soccer players in reactive agility are insufficient. Therefore, the purpose of this study was to compare speed, change of direction speed and reactive agility of junior soccer players by level of competition. Methods: Sixty-four Serbian U19 soccer players were selected and divided into an elite group (n = 29) competing in the first division of the national U19 league, and a nonelite group (n = 35) competing in a regional division. The running speed of players was determined using a 20-m sprint effort with photocell gates (Microgate. Polifemo Radio Light. Italy) placed 0.4 m above the ground, with an accuracy of 0.001 ms. The timer was automatically activated as participants crossed the first gate at the starting line with split times at 5 m. and 10 m. Change of direction speed was measured with Illinois agility test. The reactive agility test was performed according to the protocol described previously by Chaouachi et al. (2014). however, this time the Witty SEM lights were used instead the testers. When the participants past the first gate the signal shows right or left direction. The participants must react to visual signal, change direction and past the third gate. Results: There was no significant difference between competitive level in speed and change of direction speed (p> 0.05). However, large differences, favouring elite players, were observed for reactive agility time (p=0.001) and for the players` reaction (p=0.001). Conclusion: We found no clear differences in speed and change of direction speed between elite and non-elite junior soccer players in Serbia which was probably due to differential selection criteria or exposure to training. However, it can be concluded that reactive agility appeared to distinguish elite from non-elite junior soccer players.